2015
DOI: 10.1002/pssc.201510020
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of tungsten hexacarbonyl: CVD of W‐containing films under Pd codeposition and VUV assistance

Abstract: Experiments on chemical vapor deposition of W(CO)6‐derived films on silicon substrates were carried out at total pressure of 5‐10 Torr within the temperature range of 250‐350 °C; in Ar or H2 flow. Metallic, carbide and oxide phases composed the obtained films. Deposition in presence of hydrogen results in the increase of the metal content in the film. Sublimed palladium hexafluoracetylacetonate Pd(hfa)2 was used for Pd catalytic promotion of the deposition process. Codeposition with Pd(hfa)2 in hydrogen increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…As mentioned above, based on the results summarized in Figures (a–c) and S2, as well as previous reports, , ,, there is a high nucleation density when using metal–organic precursors. The W­(CO) 6 is known to thermally decompose at relatively low temperatures, compared to the ones used here and needed for the growth of highly crystalline TMDCs. This implies a very fast metal-precursor decomposition upon its introduction to the preheated reactor.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As mentioned above, based on the results summarized in Figures (a–c) and S2, as well as previous reports, , ,, there is a high nucleation density when using metal–organic precursors. The W­(CO) 6 is known to thermally decompose at relatively low temperatures, compared to the ones used here and needed for the growth of highly crystalline TMDCs. This implies a very fast metal-precursor decomposition upon its introduction to the preheated reactor.…”
Section: Results and Discussionmentioning
confidence: 99%
“…EDS showed the bulk W concentration to be 0, 1, 1.5, 2, and 3 atom % from the precursor solutions containing 0, 0.2, 0.5, 0.7, and 1 mol % of W­(CO) 6 relative to MBTC, indicating a linear increase in W concentration in the SnO 2 films with increasing W­(CO) 6 precursor and therefore operating under a mass transport-limited growth regime (Figure ). …”
Section: Resultsmentioning
confidence: 99%
“…The greatest advantage with this approach is that gas flow rates can be precisely controlled using mass flow controllers (MFCs), allowing for far greater reproducibility and much greater flexibility in the choice of tungsten precursor [30]. One common example of the latter is tungsten hexacarbonyl, W(CO) 6 , a hexacarbonyl metal precursor that is stable in air, it is a solid at room temperature and decomposes at temperatures between 600 and 900 °C in the presence of H 2 [31][32][33]. Using W(CO) 6 as a precursor Kang et al have reported the growth of continuous monolayer WS 2 films with grain sizes of * 1 lm on 4-inch fused silica substrates that exhibited carrier mobilities of 18 cm 2 /V-s [34].…”
Section: Introductionmentioning
confidence: 99%